A Comprehensive Study of Costs Associated With Recurrent Clostridium difficile Infection. (7th November 2016) - Rodrigues, Rodrigo; Barber, Grant E.; Ananthakrishnan, Ashwin N.
Abstract : BACKGROUND: Clostridium difficile infection (CDI) is the most common healthcare-associated infection and is associated with considerable morbidity. Recurrent CDI is a key contributing factor to this morbidity. Despite an estimated 83, 000 recurrences annually in the United States, there are few accurate estimates of costs associated with recurrent CDI. OBJECTIVE: We performed this study (1) to identify the health consequences of recurrent CDI including need for repeat hospitalization, intensive care unit (ICU) stay, and surgery; (2) to determine costs associated with recurrent CDI and identify determinants of such costs; and (3) to compare the outcomes and costs of recurrent CDI to those who develop reinfection. METHODS: We identified all patients with confirmed recurrent CDI between January to December 2013 at a single referral center. Healthcare burden associated with recurrence including diagnostic testing, pharmacologic treatment, and inpatient and outpatient healthcare visits were identified in the 12 months following the first recurrence. Total healthcare costs were calculated, and the predictors of high healthcare utilization were identified. RESULTS: Our study population included 98 patients with recurrent CDI. The median interval between the initial infection and recurrence was 37 days. The mean age of the cohort was 67 years, two-thirds were women (62%), and the mean Charlson index was 8.6. During the year following the first recurrence of CDI, each patient underwent a mean of 4.4 stool C. difficile toxin tests and received a mean of 2.5 prescriptions for oral vancomycin (range, 0–6). Most patients (84%) with recurrence had a CDI-related hospitalization, and 6% underwent colectomy. The mean total CDI-associated cost was $34, 104 per patient, with hospitalization costs accounting for 68%, surgery 20%, and drug treatment 8% of this cost, respectively. Extrapolating to the United States overall, we estimate an annual cost of $2.8 billion related to recurrent CDI. CONCLUSION: Recurrent CDI is associated with considerable morbidity and cost. Infect Control Hosp Epidemiol 2017;38:196–202